Enhanced recovery urinary protocol for patients undergoing hip surgery: a quasi-experimental study - Behairy, Amoura S; Al-Batanony, Manal A; Alwashmi, Emad A; Abdel Hakeim, Eglal H (The Journal of Infection in Developing Countries, 2024)
Introduction: Postoperative urinary retention (POUR) is a common complication after hip surgery. The enhanced recovery urinary protocol (ERUP) is a tool that employs several perioperative strategies to facilitate optimal conditions for surgery and recovery. The aim of this study was to evaluate the effect of ERUP on POUR in patients undergoing hip surgery. Methodology: A controlled pre- and post-quasi-experimental study was conducted. Data was collected between May 2018 and January 2019 at the orthopedic department of one of the largest teaching hospitals affiliated with Menoufia University in Egypt. A convenience sample of 100 Egyptian patients (of both genders) undergoing elective hip surgery was equally allocated into two groups. The control group (n = 50) was given traditional routine perioperative nursing care, while the intervention group (n = 50) was subjected to ERUP. Data was collected from socio-demographic, medical, and surgical data sheets, preoperative medication assessment sheets, postoperative data sheets, and fluid balance charts. Results: ERUP application significantly reduced the length of hospital stay and the incidence of POUR in the intervention group. Conclusions: Implementation of the ERUP is recommended for patients undergoing hip surgery, as it has a significantly positive effect on reducing the incidence of POUR.